Development of a highly modified asphalt with SBS polymer from a conventional base asphalt from the Ecopetrol Barrancabermeja 60-70 refinery by varying the polymer concentration (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
The present study was based on obtaining an asphalt with a torsional elastic recovery greater than 80%, from a homogenized mixture of SBS polymer with Ecopetrol Barrancabermeja 60-70 asphalt. To achieve the above, the necessary laboratory tests were carried out to verify that Colombian asphalt with high polymer content of the SBS type is compatible and in turn complies with what is proposed for the development of this research, in order to obtain an asphalt cement with elastic recoveries by torsion greater than the percentage mentioned above. Now, by incorporating 2,5%, 5,0% and 7,5% of SBS polymer to a conventional asphalt, it can be seen that the binder improves its physical properties until it reaches a highly modified asphalt (HiMA), which manages to develop an elastic recovery by torsion of 91%; this was achieved by adding 7,5% SBS polymer to the asphalt.Likewise, this study also presents the results of the laboratory test, where the elastic recovery by torsion was measured at 25 ° C for 24 hours, finding as a result a value of 94%, that is, that this type of asphalt (HiMA), with 7,5% of SBS polymer added, continues to recover through time.